2021
DOI: 10.1111/liv.15060
|View full text |Cite
|
Sign up to set email alerts
|

The improvement in body composition including subcutaneous and visceral fat reduces ammonia and hepatic encephalopathy after transjugular intrahepatic portosystemic shunt

Abstract: Background: Sarcopenia and myosteatosis have been associated to a poor prognosis of cirrhosis and to a higher incidence of hepatic encephalopathy (HE). The prognostic implications of visceral and subcutaneous adiposity are less known. Aim:To evaluate the modifications of visceral and subcutaneous adipose tissue after TIPS and to investigate their relationships with the modification of muscle mass and with the incidence of post-TIPS HE. Patients and Methods: 35 cirrhotic patients submitted to TIPS were retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 35 publications
0
40
1
Order By: Relevance
“…HVPG was found to be useful for predicting long-term mortality in patients with decompensated cirrhosis, especially in the presence of ascites ( 27 ), which may be related to acute ischemia of the liver ( 6 ). The applicability of this strategy to patients with less severe liver dysfunction is still a matter of debate ( 40 - 42 ). The TIPS procedure aims to decrease portal pressure gradient (PPG) to just <12 mmHg or at least 20% from baseline levels ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…HVPG was found to be useful for predicting long-term mortality in patients with decompensated cirrhosis, especially in the presence of ascites ( 27 ), which may be related to acute ischemia of the liver ( 6 ). The applicability of this strategy to patients with less severe liver dysfunction is still a matter of debate ( 40 - 42 ). The TIPS procedure aims to decrease portal pressure gradient (PPG) to just <12 mmHg or at least 20% from baseline levels ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, some pioneers addressed an improvement in various body composition profiles following interventional treatment. Gioia and colleagues found that sarcopenia and myosteatosis greatly improved in response to transjugular intrahepatic portosystemic shunt (TIPS) placement ( 25 ). Intriguingly, SATI significantly increased in addition to the drastic decrement pertaining to VATI, which was relevant to the amelioration of hepatic encephalopathy episodes independent of hepatic function.…”
Section: Discussionmentioning
confidence: 99%
“…30 Third, Gioia et al found that SAT contributed to handle and reduce ammonia levels, raising its role for ammonia and conversion of glutamate to glutamine by glutamine synthase. 31 Hyperammonemia results in decreased protein synthesis and increased autophagic proteolysis, and consequent sarcopenia is associated with the development of frailty. 32,33 Fourth, the adipose tissue depot is a major organ with microRNA (miRNA), and adipose miRNA profiles corresponding to body composition and functional status and predict adverse clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%